Synthesis, Characterization and Coordination Chemistry of N,N’-bis(3-pyridylmethyl)benzene-1,4-dicarboxamide with Palladium and Ruthenium Salts - Binti Idris, Nuruljannah Suhaida; Kadir, Maisara Abdul; Khandaker, Mohammad Moneruzzaman (Asian Journal of Chemistry, 2017)
N,N’-bis(3-pyridylmethyl)benzene-1,4-dicarboxamide (L) is a diamide bridging ligand. Utilization of bridging ligand such as L that exhibits amide moieties has greater potential to encapsulate anion via N-H hydrogen bonding donor groups and form metal ligand interaction via its pendant group containing pyridine-N atom. The complexes derived from this ligand also capable to form metallosupramolecular assemblies with the presence of the respective moieties. N,N’-bis(3-pyridylmethyl)benzene-1,4-dicarboxamide is synthesized from reaction between terephthaloyl chloride and 3-pyridylmethylamine in basic solution. The coordination chemistry between ligand L and two metal salts, palladium chloride and ruthenium chloride were attempted. Based on the combination of spectroscopic techniques such as CHNS, FTIR, NMR, TGA and cyclic voltammetry analysis, the molecular formula of the complexes may be suggested as: [Pd2(L)Cl4] and [Ru2(L)Cl6(H2O)4·2H2O].